2021
DOI: 10.1038/s41467-021-27548-2
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent iron and phosphorus availability controls photosynthesis through retrograde signaling

Abstract: Iron deficiency hampers photosynthesis and is associated with chlorosis. We recently showed that iron deficiency-induced chlorosis depends on phosphorus availability. How plants integrate these cues to control chlorophyll accumulation is unknown. Here, we show that iron limitation downregulates photosynthesis genes in a phosphorus-dependent manner. Using transcriptomics and genome-wide association analysis, we identify two genes, PHT4;4 encoding a chloroplastic ascorbate transporter and bZIP58, encoding a nucl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 62 publications
2
47
0
Order By: Relevance
“… Nam et al (2021) provided evidence regarding Fe deficiency induced ROS generation as well as chlorosis that becomes more pronounced in the presence of phosphorus rather than its absence, which explains the improved photosynthetic capability and overall growth of plants in this study under S.i + As + P treatment as As hinders the uptake of Fe ( Mousavi et al, 2020 ); neither the availability of P alone compensate for Fe deficit, nor does it represent a guarantee of counterbalancing As toxicity ( Begum et al, 2008 ; Abbasi et al, 2021 ). Availability of P is, tacitly assumed to be, crucial for the concentrations of elements that are imperative for metabolic processes associated with photosynthesis, biomass growth and yield formation, such as Mg ( Weih et al, 2021 ); plants colonized by S. indica combined with As and P benefitted much more than the ones without its symbiosis (i.e., As + P), not only in terms of nutrient uptake but also in the element concentration of Mg, which is indispensable for the formation of chlorophyll molecule ( Weih et al, 2021 ).…”
Section: Discussionmentioning
confidence: 69%
“… Nam et al (2021) provided evidence regarding Fe deficiency induced ROS generation as well as chlorosis that becomes more pronounced in the presence of phosphorus rather than its absence, which explains the improved photosynthetic capability and overall growth of plants in this study under S.i + As + P treatment as As hinders the uptake of Fe ( Mousavi et al, 2020 ); neither the availability of P alone compensate for Fe deficit, nor does it represent a guarantee of counterbalancing As toxicity ( Begum et al, 2008 ; Abbasi et al, 2021 ). Availability of P is, tacitly assumed to be, crucial for the concentrations of elements that are imperative for metabolic processes associated with photosynthesis, biomass growth and yield formation, such as Mg ( Weih et al, 2021 ); plants colonized by S. indica combined with As and P benefitted much more than the ones without its symbiosis (i.e., As + P), not only in terms of nutrient uptake but also in the element concentration of Mg, which is indispensable for the formation of chlorophyll molecule ( Weih et al, 2021 ).…”
Section: Discussionmentioning
confidence: 69%
“…6; Liang, 2022). COS also contains two overlapping sites with sequence complementarity for the PHT4;4 gene, which is required for phosphate-deficiency induced inhibition of iron chlorosis (Nam et al, 2021; Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have identified a previously unannotated iron-regulated long non-coding RNA gene that we named CAN OF SPINACH ( COS ). It is possible that previous gene expression studies could have misidentified the genes on the opposite strand (AT1G13608 and/or AT1G13609) as iron-regulated, and that the truly iron-regulated mRNA from the locus is actually the COS lncRNA (Rodríguez-Celma et al, 2013; Naranjo-Arcos et al, 2017; Bastow et al, 2018; Nam et al, 2021; Peixoto et al, 2021). We detected a spliced and an unspliced variant of COS in whole shoots of Arabidopsis, both of which were polyadenylated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the seedlings with uniform growth were transferred to nutrient solutions (pH = 4.5) with 50 mg/L Pb(NO 3 ) 2 and without Pb(NO 3 ) 2 , respectively ( Chen et al., 2007 ). These rice plants were then grown in a culture room with a photoperiod of 14/10 h (day/night) and a temperature of 28/25 °C for 14 days ( Nam et al., 2021 ). Shoot length (SHL) were measured using a ruler.…”
Section: Methodsmentioning
confidence: 99%
“…Plant basic leucine zipper (bZIP) transcription factors are a relatively conserved and large gene families. A number of bZIP members have been identified in the plants, animals, and yeasts ( Newman and Keating, 2003 ; Nam et al., 2021 ). Previous studies indicated that the bZIP transcription factors play significant roles as regulators in signal transduction and response to diverse biotic/abiotic stresses, such as drought, cold, heat, ABA, and salt stresses ( Weltmeier et al., 2006 ; Hossain et al., 2010 ; Liu et al., 2014 ; Li et al., 2020b ).…”
Section: Introductionmentioning
confidence: 99%